2007
DOI: 10.1111/j.1439-0426.2007.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationships of fishes captured from Izmir Bay, Central Aegean Sea

Abstract: Weight-length relationships are presented for 60 fish species captured from Izmir Bay, Central Aegean Sea. Samples were collected using bottom trawls (mesh sizes 24 mm at stretched cod-end). The b values W ¼ aL b showed a mean value of 3.027 (SE ¼ ±0.03) and more than 50% of the values ranged between 2.912 and 3.189. One species, Cepola macrophthalma, showed strong negative allometric growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 3 publications
1
43
2
1
Order By: Relevance
“…These variations in allometric coefficient for M. cordyla in the Mumbai coast might be attributed to differences in sample size and different locations 36 . Moreover, other factors including temperature, food (quantity, quality, and size), and stage of maturity may also account for the differences in allometric coefficient values of fishes [37][38][39] namely, Panda et al 11 reported isometric growth form for M. cordyla in Mumbai waters whereas our study found negative allometric growth for male, female and combined sex. The regression model fitting in the present study showed that L and W of the fish are highly correlated (r 2 = 0.90-0.96), which is consistent with Panda et al 11 .…”
Section: Length-weight Relationshipcontrasting
confidence: 51%
“…These variations in allometric coefficient for M. cordyla in the Mumbai coast might be attributed to differences in sample size and different locations 36 . Moreover, other factors including temperature, food (quantity, quality, and size), and stage of maturity may also account for the differences in allometric coefficient values of fishes [37][38][39] namely, Panda et al 11 reported isometric growth form for M. cordyla in Mumbai waters whereas our study found negative allometric growth for male, female and combined sex. The regression model fitting in the present study showed that L and W of the fish are highly correlated (r 2 = 0.90-0.96), which is consistent with Panda et al 11 .…”
Section: Length-weight Relationshipcontrasting
confidence: 51%
“…Several studies have been carried out on LWR for fish species in the Black Sea, the Sea of Marmara, the Aegean Sea and the Mediterranean Sea (Taskavak & Bilecenoglu, 2001;Filiz & Bilge, 2004;Karakulak et al, 2006;Ozaydin &Taskavak, 2006;Akyol et al, 2007;Demirhan & Can, 2007;Ismen et al, 2007;Ozaydin et al, 2007;Ilkyaz et al, 2008;Ceyhan et al, 2009;Erguden et al, 2009;Keskin & Gaygusuz, 2010). The aim of this study was to provide data on the relationship between the length and weight of species caught during a 3-year sampling period.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the change of b values depends primarily on the shape and wellbeing of the species, various factors may be responsible for that difference. According to Bagenal and Tesch (1978), Gonçalves et al (1997), Taskavak and Bilecenoglu (2001), and Özaydin and Taskavak (2006), the parameter b, unlike the parameter a, may vary seasonally, daily, and between habitats. Also gonad maturity, sex, diet, stomach fullness, health, and preservation techniques, as well as season could attribute to that difference.…”
mentioning
confidence: 99%